FAMILY LAW REFORM IN TURKEY: ANALYSIS OF THE ROLE OF MUSTAFA KEMAL ATATÜRK THROUGH PIERRE BOURDIEU'S HABITUS THEORY FRAMEWORK - Taufiq Ikram Ash Syidiqi; Rafi’aturrahman; Johari (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study aims to analyse the role of Mustafa Kemal Atatürk in the radical reform of family law in Turkey, which shifted from an Islamic legal system to a secular one. Using a normative-qualitative approach with a legislative and conceptual approach, data was collected from primary legal documents, historical archives, and relevant academic literature. Research findings indicate that Atatürk's success in enacting the Turkish Civil Code of 1926, which replaced the Ottoman Law of Family Rights (1917) and adopted the Swiss Civil Code, cannot be understood merely as an individual political decision. Using Pierre Bourdieu's theory of practice, formulated as (Habitus × Capital) + Arena = Practice, this study argues that Atatürk's reforms were a social practice shaped by the interaction between his personal disposition (habitus), accumulated capital (military, cultural, and symbolic), and the unique historical-political arena following the collapse of the Ottoman Empire. Substantive elements of reform included a total ban on polygamy, the institutionalisation of divorce through the courts, and the enforcement of equal inheritance rights between men and women. The study concluded that the secularisation of Turkish family law was a planned social engineering project, made possible by the convergence of Atatürk's modernist agency and a transformative historical arena.